(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This scientific article emphasizes the great importance of fighting corruption in the development of society. Currently, increasing the effectiveness of efforts to prevent and combat corruption in our country is becoming increasingly crucial. Do not remain indifferent to this cause. After all, building a healthy society depends on you and me